2002
DOI: 10.1046/j.1365-2036.2003.01401.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of triple therapy comprising rabeprazole, amoxicillin and metronidazole for second‐line Helicobacter pylori eradication in Japan, and the influence of metronidazole resistance

Abstract: SUMMARYBackground: The widespread use of eradication therapy for Helicobacter pylori in Japan has led to an increase in antibiotic-resistant strains and the problem of re-treatment in cases of eradication failure. Aim: To perform drug sensitivity testing for metronidazole in 92 H. pylori-positive patients who had failed eradication treatment with first-line triple therapy, consisting of a proton pump inhibitor, amoxicillin and clarithromycin, and were administered metronidazolecontaining second-line therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
99
2
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(109 citation statements)
references
References 29 publications
7
99
2
1
Order By: Relevance
“…While the implementation of an H. pylori eradication regimen in Japan was delayed compared to those in the United States and Europe, our data on present resistance rates clearly suggest that first-line eradication failure as well as resistance to CLR will continue to increase in Japan. The effectiveness of a second-line H. pylori eradication regimen consisting of PPI in combination with AMX and MNZ has been reported in Japan, with eradication success rates ranging from 80 to 90% (15,16). As confirmed by our study, the low rate of resistance to MNZ will most likely lead to the greater use of MNZ in eradication regimens in Japan.…”
Section: Discussionsupporting
confidence: 76%
“…While the implementation of an H. pylori eradication regimen in Japan was delayed compared to those in the United States and Europe, our data on present resistance rates clearly suggest that first-line eradication failure as well as resistance to CLR will continue to increase in Japan. The effectiveness of a second-line H. pylori eradication regimen consisting of PPI in combination with AMX and MNZ has been reported in Japan, with eradication success rates ranging from 80 to 90% (15,16). As confirmed by our study, the low rate of resistance to MNZ will most likely lead to the greater use of MNZ in eradication regimens in Japan.…”
Section: Discussionsupporting
confidence: 76%
“…[1][2][3] The first-line regimen for the treatment of H. pylori infection in Japan is triple therapy with a proton pump inhibitor (PPI), amoxicillin, and clarithromycin, whereas the secondline regimen consists of a PPI, amoxicillin, and metronidazole. 4,5 However, 2-3% of patients with H. pylori strains that are resistant to both first-and second-line regimens require third-line eradication therapy. 6,7 In addition, we previously showed that eradication could be achieved in about 80% of patients with seven-day 1 sitafloxacin-based triple therapy as a third-line regimen.…”
Section: Introductionmentioning
confidence: 99%
“…When the results of PPI/AC therapy are unsuccessful, the proportion of CAM-resistant patients increases after the treatment. Murakami, Sato et al, (2001) and Tankovic, Lamarque et al, (2001) reported percentages of CAM-resistant patients were 66.2% and 70%, respectively. The other issue is that PPI/AC therapy is only approved for reimbursement by the national health insurance in Japan as a secondary eradication regimen.…”
Section: Discussionmentioning
confidence: 95%
“…However in Brazil, the proportion of AMPC-resistant bacteria was 29% (Mendonca, (Murakami, Sato et al, 2001, Adamek, Suerbaum et al, 1998. It has been reported that the mechanism of AMPC resistance is (Dore, Graham et al, 1999, Okamoto, Yoshiyama et al, 2002.…”
Section: Discussionmentioning
confidence: 99%